GENETIC MARKERS OF METABOLIC SYNDROME AND CORONARY ATHEROSCLEROSIS IN YAKUTIA INHABITANTS - А. N. Romanova; М. I. Voevoda; V. N. Maksimov (Российский кардиологический журнал)
Aim. Evaluation of the association  of rs17465637 gene  MIA3 (1q41),  rs4804611 gene  ZNF627 (19p13.2),   rs2549513   (16q23.1),   rs619203   gene  ROS1  (6q22), rs1333049 (9p21.3), rs1376251 gene TAS2R50 (12p13.2) with arterial hypertension (AH), myocardial   infarction  (MI),  metabolic   syndrome   (Ms)   and   coronary atherosclerosis (CAS) in Yakutia inhabitants depending  on ethnicity and gender.Material and methods. The results analyzed, of the assessment of the patients with verified CAS (396 males, 60 females) and persons with no clinical signs of CHD (212 males, 271 females)  age 45-64 y.o., from native and non-native Yakutia ethnicities. The period of the study: 2007-2010 years. Genomic DNA was extracted  from venous blood by phenol-chlorophorm method.  Genes  polymorphism was tested with PCR real  time  according   to  the  manual  of the  equipment   (probes   TaqMan  ,  Applied Biosystems, USA) on the device ABI 7900HT. In the study, the following mononucleotide polymorphisms  were  included  (MNP): rs17465637 gene  MIA3,  rs4804611   gene ZNF627, rs2549513  (chr. 16), rs619203  gene ROS1, rs1333049  (chr. 9), rs1376251 gene TAS2R50. For diagnosis of Ms, IDF 2005 criteria were applied.Results. Association of AH was found in native inhabitants — males with genotype СС rs1376251  gene  TAS2R50 (p=0,004),  in females  with АА rs2549513  (chr. 16) (p=0,028)  and  rs4804611   gene   ZNF627  (p=0,033);  in non-native  inhabitants (regardless the gender and in females) — rs619203 gene ROS1 (p=0,000). Relation was found for MI in native inhabitants with genotype  ТТ rs1376251  gene  TAS2R50 (p=0,005); in non-native heterozygous males rs17465637 gene MIA3 (p=0,047) and rs619203 gene ROS1 (p=0,009), as homozygous АА rs2549513 (chr. 16) (p=0,041). The associations were found for Ms among  native inhabitants  in male carriers  of genotypes АА rs17465637 gene MIA3 (p=0,029) and heterozygous rs4804611 gene ZNF627 (p=0,034),  as  heterozygous regardless the  gender  rs2549513  (chr.  16) (p=0,016) in non-native inhabitants in male (p=0,016) and female (p=0,005) carriers of  GG rs619203   gene   ROS1  and  heterozygous  females   rs1333049   (chr.  9) (p=0,031).  With the  CAS,  the  association   found  in native  heterozygous males rs17465637 gene  MIA3 (p=0,040)  and  carriers  of ТТ rs1376251  gene  TAS2R50 (p=0,006);  in non-native  males  with CG rs619203  gene  ROS1 (p=0,020),  in nonnative females with  АА rs4804611 gene ZNF627 (p=0,008), heterozygous rs1333049 (chr. 9) (p=0,030) and rs2549513  (chr. 16) (p=0,024).Conclusion. First time in inhabitants of Yakutia REpublic, the genome  wide results replicated,  of the association  study with AH, MI, Ms, CAS. These genetic  markers can  be  utilized for the  risk assessment of cardiovascular   diseases in Russian (Yakutia) population.